HUBUNGAN ANTARA KELUARGA BROKEN HOME, POLA ASUH ORANG TUA DAN INTERAKSI TEMAN SEBAYA DENGAN KENAKALAN REMAJA - Sujoko, Sujoko (2011)
The transition can lead to the crisis that is usually indicated by the indication of the emergence of juvenile delinquency. The objectives of this research were; (1) To find out empirically the relationship of broken home family, parent up bringing pattern, and interaction of friend of the same age to juvenile delinquency. (2) To find out the effective contribution of broken home family, parent up bringing pattern and interaction of friend of the same age to juvenile delinquency. Populations of this research were students of Tekno-SA vocational high school Surakarta and the numbers of sample were 119 students. Research's sample was taken using cluster random sampling. The collecting data method used were scales of juvenile delinquency, broken home family, parent up-bringing pattern, and interaction of friend of the same age. Analyzing data technique used was double regressive analysis. Based on the analysis it was found that R=0,429, R2 =0,184, and F=8,623 with p=0,000 (p<0,01). This result showed that there was significant positive correlation between broken home family, parent up-bringing pattern, and interaction of friends of the same age to the juvenile delinquency and these variables gave effective contribution as big as 18,4% to juvenile delinquency variable. Broken home family gave effective contribution as big as 7,8%, parent up-bringing pattern gave effective contribution as big as 8,5%, and interaction of friends of the same age gave effective contribution as big as 5,6%.